The diagnostic accuracy of nanopore sequencing in Tuberculous Lymphadenitis: Systematic review and meta-analysis protocol - Liwei Yao; Caifang Bu; Lijun Xiang (PLoS ONE, 2025)
Background Tuberculous lymphadenitis (TL) is a common case of extrapulmonary tuberculosis caused by Mycobacterium tuberculosis (MTB). The current use of nanopore sequencing in TL is limited. The aim of our study is to complete a systematic review and meta-analysis protocol to assess the performance of nanopore sequencing in TL. Methods English databases (including Medline via PubMed, Cochrane Library, and Embase) and Chinese databases (including Wanfang Database and China National Knowledge Infrastructure) will be searched for literature related to the research topic. We designed eligibility criteria based on PICT (Population, Index Test, Comparator Test and Target Condition). We will extract relevant data from the included articles when they have been identified. The quality of the studies will be assessed using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) tool. We will use midas package in STATA for the calculation of the pooled effect values and the corresponding forest plots when the final number of included studies is more than four, and Meta-DiSc for the calculation of the pooled effect values and the forest plots when the number of included studies is less than four. When the results of different reference gold standards are reported simultaneously in the same literature, we will extract the corresponding TP, FP, FN, and TN values according to the different reference gold standards and analyze them independently. I2 statistic will be used to quantify inter-study heterogeneity. If substantial heterogeneity (I² > 50%) is detected, potential sources will be investigated through subgroup, meta-regression, and sensitivity analysis. Conclusion We conducted this protocol according to the guidelines and submitted it to a peer-reviewed journal to improve our protocol through peer review and ultimately better guide the completion of the systematic review and meta-analysis. Systematic review registration PROSPERO Registration number: CRD42024595521